Early outcomes of modified hockey-stick medial plate in the treatment of Schatzker IV-VI tibial plateau fractures: a retrospective controlled study - Xiao Wang; Zhangyu Zhu; Zhaowei Yin; Haibo Xu; Dongdong Jiang; Haonan Xiu; Junwei Yan; Bin Liang (Journal of Orthopaedic Surgery and Research)
Abstract Background Schatzker IV–VI tibial plateau fractures usually happen in the weight-bearing part of the knee joint. They are hard to fix with traditional methods because they damage soft tissues and make it hard to get back to normal activities. This study introduces a modified hockey-stick medial plate (mHSMP) designed to improve functional outcomes while reducing surgical complexity. Methods This retrospective study included 40 patients with Schatzker IV-VI tibial plateau fractures (20 in the experimental group treated with the mHSMP and 20 in the control group treated with a traditional medial plate) who were followed up for 12 months. Surgical time, intraoperative blood loss, fracture healing time, postoperative complications, and knee function, as assessed by the Hospital for Special Surgery (HSS) score, were compared between the two groups. Results Compared with the control group, the experimental group had significantly greater HSS scores at 3 days postsurgery (50.2 ± 1.7 vs. 43.6 ± 1.8, P < 0.001), 3 months (68.2 ± 1.8 vs. 61.7 ± 1.9, P < 0.001), and 6 months (83.2 ± 1.9 vs. 76.7 ± 2.1, P < 0.001). No significant differences were observed between the two groups in terms of surgical time, intraoperative blood loss, fracture healing time, or postoperative complications. Conclusion Compared with traditional fixation methods, the mHSMP results in superior early functional recovery with comparable safety, providing an effective alternative for treating Schatzker IV-VI tibial plateau fractures.